Combined heterotopic liver–pancreas transplantation as a curative treatment for liver cirrhosis and diabetes mellitus in cystic fibrosis. (18th October 2013) - Henn, Constance; Kapellen, Thomas; Prenzel, Freerk; Siekmeyer, Manuela; Hau, Hans‐Michael; Kiess, Wieland; Bartels, Michael
Abstract Cystic fibrosis (CF) is an inherited disease with a defect in epithelial chloride transport that results in a multisystem disease. Although pulmonary disease remains the primary cause of morbidity and mortality, focal biliary cirrhosis and portal hypertension may develop in up to 8% of these patients. Liver transplantation (TX) is an accepted therapy and shows good results. We report on a patient with cystic fibrosis homozygous for the most common CFTR mutation delta F 508 who received a combined heterotopic liver and pancreas transplantation at the age of 18 yr. He suffered from CFRD, which untypically required high doses of insulin. In addition, the patient had pulmonary complications, was chronically colonized with multiresistant Pseudomonas aeruginosa (MBL) and had an allergic bronchopulmonary aspergillosis (ABPA). The patient remained in stable health for 54 months post‐TX and was able to live a nearly normal life. With a follow‐up of five yr, the function of the liver and pancreas allografts was excellent. However, and sadly, his pulmonary function continued to deteriorate from progression of his CF, and he died of respiratory failure due to a severe pneumonia and septicemia at the age of 23 yr and five months.